Outcomes of Total Knee Arthroplasty in Human Immunodeficiency Virus-Positive Patients - Roof, Mackenzie A.; Anoushiravani, Afshin A.; Chen, Kevin K.; Moses, Michael J.; Wolfson, Theodore; Poultsides, Lazaros; Schwarzkopf, Ran (The Journal of Knee Surgery, 2020)
Successful management of human immunodeficiency virus (HIV) has lengthened the life expectancy of HIV-positive (HIV + ) patients; consequently, increasing numbers of this patient population are candidates for total knee arthroplasty (TKA). This study seeks to provide detailed results of TKA in HIV+ patients and compare them to an HIV-negative (HIV − ) cohort. We performed a multicenter retrospective case–control study comparing 25 HIV+ patients to 25 HIV− patients undergoing TKA. The analysis included a cohort and subgroup stratification based on the presence or absence of postoperative complications. Prior to TKA, all 25 patients had a documented history of HIV infection. No intraoperative complications were reported. Ninety-day postoperative complications included knee contracture (one HIV + , no HIV − , p = 0.3124), periprosthetic joint infection requiring revision (one HIV + , no HIV − , p = 0.3124), mechanical fall requiring incision and drainage (one HIV + , no HIV − , p = 0.3124), and death (one HIV + , no HIV − , p = 0.3124). The average follow-up was 18.80 months. HIV+ patients stayed in the hospital for an average of 3.8 days following surgery, which was significantly greater than HIV− patients (2.28 days; p = 0.0040). As the life expectancy for HIV+ patients improves, a greater number will be TKA candidates. This study has shown an acceptable postoperative complication risk in an HIV+ patient population undergoing TKA, albeit with a significantly increased hospital length of stay.
Keywords: total knee arthroplasty; human immunodeficiency virus; postoperative outcomes; complications